2019
DOI: 10.1021/acs.jpcc.9b01253
|View full text |Cite
|
Sign up to set email alerts
|

Free Surface-Induced Glass-Transition Temperature Suppression of Simulated Polymer Chains

Abstract: Glass-transition temperatures (T g’s) in poly­(ethylene oxide) chains of 250 monomers as typical examples have been extensively simulated with the systematically coarse-grained potentials. The studied model systems include two 1-chain systems without and with the periodic boundary condition and two 8-chain systems in the NVT and NPT ensembles, which are labeled as nopbc, pbc, NVT, and NPT, respectively. The absence of crystallization and instead the occurrence of glass transition are first confirmed for all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
4
9
0
Order By: Relevance
“…These observations are consistent with previous experimental and simulation reports of high mobility in the surface layer of metallic glasses near the T g,v , ,, which is similar to the picture of a liquid surface that persists below the T g,v that has been extensively developed for molecular and polymeric glasses. ,, Our results expand upon this picture by adding metallic glasses to the materials exhibiting these phenomena, directly measuring the surface layer thickness, and demonstrating spatial heterogeneity. We also introduce the idea of and measure T g,s , the temperature at which the surface falls out of equilibrium and becomes glassy.…”
Section: Resultssupporting
confidence: 92%
“…These observations are consistent with previous experimental and simulation reports of high mobility in the surface layer of metallic glasses near the T g,v , ,, which is similar to the picture of a liquid surface that persists below the T g,v that has been extensively developed for molecular and polymeric glasses. ,, Our results expand upon this picture by adding metallic glasses to the materials exhibiting these phenomena, directly measuring the surface layer thickness, and demonstrating spatial heterogeneity. We also introduce the idea of and measure T g,s , the temperature at which the surface falls out of equilibrium and becomes glassy.…”
Section: Resultssupporting
confidence: 92%
“…In the present work, three different methods via the computation of volumetric, energetic properties, and conformational transition of torsion angles (the characterization of conformational transition was exhibited in SI) were used to determine precisely the T g of silicone copolymer. These methods were applied in earlier studies to compute T g , and the simulated results were found to be consistent with the experimental results. , It was expected that the introduction of epoxy groups restricts the mobility of polymer segments and reduces the free volume in the rubber region . The assumption was validated by the results shown in Figure (a).…”
Section: Results and Discussionsupporting
confidence: 59%
“…These methods were applied in earlier studies to compute T g , and the simulated results were found to be consistent with the experimental results. 26,43 It was expected that the introduction of epoxy groups restricts the mobility of polymer segments and reduces the free volume in the rubber region. 50 The assumption was validated by the results shown in Figure 2(a).…”
Section: Preparation Of Epoxy-methyl-ethyl-vinyl Silicone Elastomer (...mentioning
confidence: 76%
See 1 more Smart Citation
“…Confinement of polymer chain mobility is well investigated by other authors. Often, the glass transition temperature is determined experimentally as a function of the distance to the substrate. Also, molecular dynamics simulations support the experimental observations. , Depending on the polymer and the measurement technique, the substrate influences polymer chain mobility up to a distance of 5 to 10 nm to the substrate. As the diffusion coefficient is a measure of polymer chain mobility, this contradicts the observations of Buss et al and Vogt et al that the diffusion is slowed down in a range of even up to 40 nm (Buss et al) or 150 nm (Vogt et al) from the substrate due to confinement of polymer chains.…”
Section: Introductionmentioning
confidence: 97%